The effect of synthesis time on morphology and electronic structure of polyaniline - I. A. Lobov; I. K. Shulus (Омский научный вестник)
The paper investigates the morphology and electronic structure change of polyaniline as a function of the synthesis time. It is shown that the band gap of a polymer decreases with increasing duration of the synthesis time due to a change in the number of electronic states in a growing molecular coil. It is shown, that a longer synthesis provides a large amount of work function as a result of an increase in the protonation degree of polyaniline.